Strength and Durability of Cement Stabilized Expansive Soil Amended with Sugarcane Press Mud - James, Jijo; Selvam, Akilan Gunaselvi; Annamalai, Krishna Khumaar; Marimuthu, Vishal; Srinivasan, Vishnu Varadhan; Kolamurugan, Sooraj (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The present investigation delved into the performance of cement stabilized soil amended with sugarcane press mud (PM), an organic waste residue from the sugar industry. An expansive soil was stabilized using 3% and 8% ordinary Portland cement (OPC) and modified with 1%, 3% and 5% PM. Cylindrical samples of dimensions 38 mm diameter and 76 mm height were cast and cured for 7, 14 and 21 days for all combinations considered.
Keywords: soil stabilization; sugarcane; waste; durability; stabilizacja gruntu; odpady; trzcina cukrowa; trwałość; wytrzymałość